2011
DOI: 10.1007/s00415-011-5981-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolated thalamic agraphia with impaired grapheme formation and micrographia

Abstract: Two patients with isolated thalamic agraphia are described. Both showed kanji (Japanese morphograms) agraphia due to impaired character recall, grapheme deformity and micrographia (progressive reduction in character size during writing) after a lesion that involved the ventral lateral and ventroposterolateral nuclei. Single photon emission computed tomography with a (99m)Tc-ethylcysteinate dimer revealed hypoperfusion in the left precentral gyrus (Brodmann Area 6) and anterior supramarginal gyrus in both. Six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…, a diaschisis phenomenon). 22,30 Similar to our patient, previously reported cases of pure apraxic agraphia, 31 pure agraphia, 23,32,33 and alexia with agraphia 11 due to a thalamic lesion have shown hypofunction in the ipsilateral cerebral hemisphere. Araki et al , reported two patients with alexia with agraphia due to left thalamic strokes involving the territory of the tuberothalamic and paramedian arteries (lesion involved the DM nucleus in both cases).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…, a diaschisis phenomenon). 22,30 Similar to our patient, previously reported cases of pure apraxic agraphia, 31 pure agraphia, 23,32,33 and alexia with agraphia 11 due to a thalamic lesion have shown hypofunction in the ipsilateral cerebral hemisphere. Araki et al , reported two patients with alexia with agraphia due to left thalamic strokes involving the territory of the tuberothalamic and paramedian arteries (lesion involved the DM nucleus in both cases).…”
Section: Discussionsupporting
confidence: 90%
“…Cognitive impairment may be a secondary consequence of a deactivated or disengaged cortex. 22 The diaschisis phenomenon in thalamic hemorrhages may be temporary, with gradual improvement in the function of the affected area, 23 but can also be persistent. 24 …”
Section: Discussionmentioning
confidence: 99%
“…The thalamic involvement in this girl brings us back to the few reported cases of adult patients with isolated thalamic agraphia with impaired grapheme formation and micrographia due to a lesion in ventral and ventroposterolateral nuclei in the left thalamus or with pure agraphia or with alexia and agraphia due to left thalamic bleeding [2][3][4]. All these authors suggest a potential role of the thalamus in writing disorders with secondary negative effect of the lesion on the function of left cerebral cortex.…”
Section: Discussionmentioning
confidence: 95%
“…The putamen segregation between simple and complex movements would fit a general organization of parallel cortico-basal ganglia loops described for motor and non-motor functions [ 94 ]. The left thalamic activations that were seen not only in right- but also in left-hand writing, contrasted to tapping, points at an aspect of writing beyond movement characteristics [ 95 97 ]. Such left thalamic function is anatomically consistent with its position as an outflow target of the right cerebellum and would thus functionally mediate non-motor functions of right posterior cerebellar lobe as described in the previous paragraph.…”
Section: Discussionmentioning
confidence: 99%